Entangled histories of the Balkans. - Vezenkov, Alexander; Daskalov, Rumen (Balkan studies library., 2015)
Modern Balkan history has traditionally been studied by national historians in terms of separate national histories taking place within bounded state territories. The authors in this volume take a different approach. They view the modern history of the region from a transnational and relational perspective in terms of shared and connected, as well as entangled histories. This regards the treatment of shared historical legacies by rival national historiographies. The volume deals with historiograpical disputes that arose in the process of ¿́¿nationalizing¿́¿ the past. Contributors include: Diana Mishkova, Alexander Vezenkov, Roumen Daskalov, Tchavdar Marinov and Bernard Lory.